2021
DOI: 10.2147/cia.s336802
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study Examining Self-Regulation Practices in Older Drivers with and without Suspected Mild Cognitive Impairment

Abstract: Purpose Mild cognitive impairment can impact driving performance and self-regulation practices. However, there is little evidence on how cognitive impairment may impact these self-regulation practices over a period of time. Therefore, the aim of this study was to examine changes in the number and type of situations in which older drivers with and without suspected mild cognitive impairment (MCI) self-regulate their driving over a one-year period, after accounting for relevant confounders. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…The study established a direct negative effect of age on the formation of the metacognitive feeling of certainty, indicating that older individuals diagnosed with MCI tend to exhibit less confidence in their ability to accomplish driving tasks under discussion. This finding aligns with existing literature, where age has been identified as a significant factor influencing decisions related to driving, with older age correlating with a higher likelihood of self-regulation or cessation of driving altogether [ 32 , 36 , 40 , 41 , 61 ]. The diminished certainty observed with increasing age may be attributed to a general decline in health and functional abilities typically associated with age [ 38 , 62 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study established a direct negative effect of age on the formation of the metacognitive feeling of certainty, indicating that older individuals diagnosed with MCI tend to exhibit less confidence in their ability to accomplish driving tasks under discussion. This finding aligns with existing literature, where age has been identified as a significant factor influencing decisions related to driving, with older age correlating with a higher likelihood of self-regulation or cessation of driving altogether [ 32 , 36 , 40 , 41 , 61 ]. The diminished certainty observed with increasing age may be attributed to a general decline in health and functional abilities typically associated with age [ 38 , 62 ].…”
Section: Discussionsupporting
confidence: 91%
“…Women seem to be more capable of recognizing changes in driving and tend to be more accurate in their self-reports, viewing driving as a mutable skill, in contrast to men, who see driving as a static skill [ 38 , 39 ]. Consequently, women may favor a metacognitive approach to their cognitive capabilities involved in driving, impacting the greater number of driving situations in which they self-regulate [ 40 , 41 , 42 ]. However, the greater discomfort and lesser need for driving may also influence women’s adoption of driving regulations rather than metacognitive awareness alone [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stringent licensing policies are imposed on older drivers because their driving abilities could be affected by functioning difficulties as they age. However, it is reported that older drivers adjust their driving by driving less or avoiding challenging situations, compensating for their declining abilities [4][5][6] and potentially attenuating their MVC risk. Nevertheless, older drivers in Japan are not only required to take driving lessons and cognitive screening tests at their license renewal but are further encouraged to surrender their driving licenses.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the quality of many of the skills should be measured with reliable instruments for vulnerable people [ 10 , 11 ]. These skills are also necessary as safe driving performance decreases [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ], which is reflected in crash rates and their severity. The involvement of older people in fatal accidents is estimated to increase by 155% by 2030, accounting for 54% of the total projected increase in the number of total fatal accidents [ 19 ].…”
Section: Introductionmentioning
confidence: 99%